Analisis Faktor-faktor yang mempengaruhi penurunan disiplin kerja pegawai pada kelompok hukum organisasi dan Kepegawaian pada Badan Penyuluhan dan Pengembangan Sumber Daya Manusia Pertanian (BPPSDMP) Kementerian Pertanian RI di Jakarta - Ardiansyah Saputra; Syarif Ali (Politeknik Ganesha Medan, 2022)
Work discipline is an important thing to pay attention to. Work discipline will be easily seen in employees who have a high sense of responsibility. This research is a qualitative research that aims to describe the work discipline of employees at the Agricultural Extension and Human Resources Development Agency (BPPSDMP) of the Indonesian Ministry of Agriculture in Jakarta. Data collection in this research was carried out by interview, observation and documentation methods. Interviews were conducted in a semi-structured manner with six participants, including one coordinator of the legal group organizational and the staffing group, two sub-coordinators, two staff from each legal group organizational and the staffing group also one sub-coordinator of State Property that receiving services from the legal group organizational and the staffing group. To prove the validity of the data in the research, the researcher used the data triangulation method. Furthermore, the data is analyzed by performing data reduction, data presentation and drawing conclusions. The results of the research found two main factors that influence the decrease in employee discipline. definite rules that can be used as guidance and supervision of leaders in the workplace. Remote work during the covid-19 pandemic has also changed work styles from before, as the cause of the decrease in employee work discipline in the legal group organizational and the staffing group at the agricultural extension and human resource development agency (BPPSDMP) of the Indonesian Ministry of Agriculture in Jakarta.